Effect of Lipophilicity on Microneedle‐Mediated Iontophoretic Transdermal Delivery Across Human Skin In Vitro. Issue 10 (17th August 2013) - Pawar, Kasturi R.; Smith, Forrest; Kolli, Chandra Sekhar; Babu, R. Jayachandra
<x xml:space="preserve">Abstract</x> The effect of lipophilicity of drug on the microneedle (MN)‐mediated iontophoretic delivery across dermatomed human skin was studied. Beta blockers with similar pKa but varied log P values were selected as model drugs in this study. Iontophoresis (ITP) or MNs, when used independently, increased the transdermal flux of beta blockers as compared with passive delivery (PD). ITP across the MN‐treated skin (MN + ITP) increased the permeation rate of all beta blockers as compared with PD (p < 0.001). The enhancement ratios (ER) for hydrophilic molecules (atenolol and sotalol) were 71‐ and 78‐fold higher for ITP + MN as compared with PD. However, for lipophilic molecule such as propranolol, there was 10‐fold increase in the ER as compared with PD. These observations were further substantiated by the skin retention data; an inverse relationship between the skin retention and the hydrophilicity of the drug was observed. The results in the present study point out that the lipophilicity of the molecule plays a significant role on the electrically assisted transdermal delivery of drugs across the microporated skin. Using the combination of ITP + MN, hydrophilic drugs (atenolol and sotalol) were delivered at a much higher rate as compared with lipophilic molecules (propranolol and acebutolol). © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3784–3791, 2013